Polarization of eigenmodes in laser diode waveguides on semipolar and nonpolar GaN - Rass, Jens; Wernicke, Tim; Scheibenzuber, Wolfgang G.; Schwarz, Ulrich T.; Kupec, Jan; Witzigmann, Bernd; Vogt, Patrick; Einfeldt, Sven; Weyers, Markus; Kneissl, Michael (Physica Status Solidi-Rapid Research Letters, 2010)
Recent calculations of the eigenmodes in waveguides grown on semipolar GaN suggest that the optical polarization of the emitted light as well as the optical gain depends on the orien- tation of the resonator. Our measurements on separate confinement heterostructures on semipolar (1122) and (1012) GaN show that for laser resonators along the semipolar [1123] and [0111] directions (i.e. the projection of the c-axis onto the plane of growth) the threshold for amplified spontaneous emission is lower than for the nonpolar direction and that the stimulated emission is linearly polarized as TE mode. For the waveguide structures along the nonpolar [1100] or [1120] direction on the other hand, birefringence and anisotropy of the optical gain in the plane of growth leads not only to a higher threshold but alsoto a rotation of the optical polarization which is not any more TE- or TM-polarized but influenced by the ordinary and extraordinary refractive index of the material. We observe stimulated emission into a mode which is linearly polarized in extraordinarydirection nearly parallel to the c-axis.© 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11